1993
DOI: 10.1210/endo.133.3.8365352
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids: 3 alpha-hydroxy-5 alpha-pregnan-20-one and its precursors in the brain, plasma, and steroidogenic glands of male and female rats.

Abstract: A RIA procedure for measuring progesterone (PROG), 5 alpha-pregnane-3,20-dione (5 alpha-DH PROG), and 3 alpha-hydroxy-5 alpha-pregnan-20-one (3 alpha,5 alpha-TH PROG) has been developed and validated by GLC/mass spectrometry. Measurements were made in intact and adrenalectomized (ADX) male rats, in cyclic, pregnant, spayed, and spayed-ADX females, and in both males and spayed females injected with PROG. The predominant contribution of the ovary to the concentrations of 3 alpha,5 alpha-TH PROG in plasma and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(91 citation statements)
references
References 13 publications
7
80
2
2
Order By: Relevance
“…The concentrations at which steroid hormones modulate nAChR activity are in the tens of micromolar, i.e., three to five orders of magnitude higher than those found in the mammalian brain (Backstrom et al, 1976;Corpechot et al, 1993;Bixo et al, 1997). However, the actual concentrations of steroids at synapses or neuronal compartments bearing steroid-sensitive membrane receptors can be substantially higher than the CSF or tissue concentrations of the hormones.…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 90%
“…The concentrations at which steroid hormones modulate nAChR activity are in the tens of micromolar, i.e., three to five orders of magnitude higher than those found in the mammalian brain (Backstrom et al, 1976;Corpechot et al, 1993;Bixo et al, 1997). However, the actual concentrations of steroids at synapses or neuronal compartments bearing steroid-sensitive membrane receptors can be substantially higher than the CSF or tissue concentrations of the hormones.…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 90%
“…These observations are consistent with findings from studies performed in the adult rat (Corpechot et al 1993). The plasma concentrations of these steroids in the intact fetuses were similar to those we have reported previously , Nguyen et al 2003a).…”
Section: Discussionsupporting
confidence: 93%
“…Using this methodology, allopregnanolone concentrations in cortical homogenates were estimated to be ~1-2 ng/g in juvenile, ~1 ng/g in diestrous, 4-6 ng/g in estrous, and 4-8 ng/g in proestrous females, with levels reaching ~10-30 ng/g during pregnancy (Paul and Purdy, 1992;Corpéchot et al, 1993;Concas et al, 1998;Kellogg and Frye, 1999). These assessments have been used to estimate that allopregnanolone levels are diestrus females (Paul and Purdy, 1992), but can reach ~100 nM during the late stages of pregnancy (see for example; Brussaard et al, 1997;Lambert et al, 2003).…”
Section: Neurosteroid and Anabolic Androgenic Steroid Levels In The Cnsmentioning
confidence: 99%
“…Corpéchot et al (1993) reported that allopregnanolone was below the limit of detection in the adult male rat brain. In contrast, Kellogg and Frye (1999) reported levels of allopregnanolone in brain extracts from adult males of 3.3 ng/g; a concentration only slightly lower than that they reported for estrous females and comparable to that which they found for 3α-diol in males (3.2 ng/g).…”
Section: Neurosteroid and Anabolic Androgenic Steroid Levels In The Cnsmentioning
confidence: 99%